2011
DOI: 10.1152/ajpcell.00061.2010
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-induced permeability transition in rat brain mitochondria is promoted by carbenoxolone through targeting connexin43

Abstract: Azarashvili T, Baburina Y, Grachev D, Krestinina O, Evtodienko Y, Stricker R, Reiser G. Calcium-induced permeability transition in rat brain mitochondria is promoted by carbenoxolone through targeting connexin43.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
46
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 45 publications
2
46
0
Order By: Relevance
“…Our data showed that Cbx altered the parameters of mPTP function by shortening the lag time of MPT onset (lowering the capacity to retain Ca 2+ in the matrix) and initiating Ca 2+ -induced Ca 2+ efflux from the mitochondrial matrix [6]. Cbx increased Ca 2+ -induced high amplitude swelling of both RBM and RLM.…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations
“…Our data showed that Cbx altered the parameters of mPTP function by shortening the lag time of MPT onset (lowering the capacity to retain Ca 2+ in the matrix) and initiating Ca 2+ -induced Ca 2+ efflux from the mitochondrial matrix [6]. Cbx increased Ca 2+ -induced high amplitude swelling of both RBM and RLM.…”
Section: Introductionmentioning
confidence: 96%
“…Recently, we compared the mechanism of action of Cbx on Ca 2+ -induced mPTP opening in rat brain mitochondria (RBM, synaptic and non-synaptic) and rat liver mitochondria (RLM), in an attempt to identify the mitochondrial target of Cbx [6]. Our data showed that Cbx altered the parameters of mPTP function by shortening the lag time of MPT onset (lowering the capacity to retain Ca 2+ in the matrix) and initiating Ca 2+ -induced Ca 2+ efflux from the mitochondrial matrix [6].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The formation of the mitochondrial permeability transition pore (PTP) triggered by Ca 2+ overload or reactive oxygen is well documented [27][28][29][30]. This might happen by excitotoxicity including excessive glutamate release from depolarized neurons or dead cells, which causes permanent activation of glutamate receptors and persistent increase in the cytosolic Ca 2+ concentration [31][32][33].…”
Section: Introductionmentioning
confidence: 99%